Influence Utilization Assignment-Based Project About the History of the Old City To Motivation Studying History for Class XI SMA Negeri 3 Semarang - Septiyaningsih, Imada Cahya (Indonesian Journal of History Education, 2019)
History learning has a vital role in developing students' knowledge. However, it often faces challenges such as a lack of interest, which can make students feel bored, and often repeated material. This research uses a quantitative approach with an experimental design to identify students' learning motivation in history subjects in class XI SMA Negeri 3 Semarang, both in groups that receive project-based learning and those that do not. The research results showed that the average pre-test score for the experimental class was 114.125, and for the control class was 110.125. Analysis of the coefficient of determination shows that around 24% of the variation in learning motivation can be explained using project-based learning. In contrast, the remainder, 76%, is influenced by other factors not examined in this study. These findings confirm that project-based learning significantly impacts students' learning motivation in the context of history learning in high schools and can provide valuable insights for developing more effective and engaging learning strategies in the future.